Photocatalysis of 17α-ethynylestradiol and estriol in water using engineered immersible optical fibres and light emitting diodes. (February 2020) - Sornalingam, Kireesan; McDonagh, Andrew; Canning, John; Cook, Kevin; Johir, Md Abu Hasan; Zhou, John L.; Ahmed, Mohammad Boshir
Graphical abstract: Highlights: Optical fibre was modified to enable side emission of light. Immersible LED is suitable as light sources for underwater photocatalysis. Au-TiO2 catalyst degraded EE2 and E3 under UVA and visible light. EE2 t1/2 was 1.26 h and 0.78 h for P25 and 4 wt .% Au-TiO2 under UVA. Optical fibre reactor showed good reusability with 94 % efficiency after 3 cycles. Abstract: This research aims to promote photocatalysis of endocrine disrupting chemicals (EDCs) in water. Two reactor setups with (i) modified air-clad optical fibres and (ii) waterproof LED strips were utilised to transmit light to photocatalysts P25 TiO2 and gold-modified TiO2 (Au-TiO2 ). The performances to photodegrade 17α-ethynylestradiol (EE2) and estriol (E3) under Cool White and UVA high efficacy LEDs were examined. Au-TiO2 showed superior photocatalytic activity for EE2 removal over P25 TiO2 . The pseudo first-order rate constants for EE2 photocatalysis under UVA were 0.55 h −1 and 0.89 h −1 for TiO2 and Au-TiO2, respectively. E3 was effectively degraded by Au-TiO2 in the immersible LED strip reactor (0.13 h −1 ).